PENGEMBANGAN ALAT ASESMEN AWAL MELALUI INSTASTORY GUNA MENENTUKAN GAYA BELAJAR SISWA KELAS XI SMA - Muhammad Zidni Ridlo; Didik Dwi Prasetya; Ahmad Yusuf Setiawan; Nadiah Alma Ratnaduhita; Adi Wahyu Wardani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Effective learning requires a way to understand the characteristics of students well, one of which is by understanding their learning styles. Therefore, the purpose of this study is to develop an initial assessment tool through instastory to determine the learning styles of students in grade XI SMA. the procedure used in this study is the ADDIE model development procedure this procedure consists of several steps namely analysis, design, development, implementation, and evaluation. In this study, data collection instruments through expert validation sheets. After going through the validation process, the next step is to analyze the data. In the media expert validation test, it obtained an average value of 92% with a statement that the media was valid / feasible to use, and the results of the material validation test obtained an average of 88% which stated that the material was valid / feasible to use. Then it was tested on students with an average result of 88% with a fairly valid category. Therefore, this initial assessment tool through instastory can be used as an interesting and solutive initial assessment tool in determining students' learning styles.